The Atlas of Cultural Heritage of the Polish Village (a Project) - Zygmunt Kłodnicki; Agnieszka Pieńczak (Studia Etnologiczne i Antropologiczne, 2019)
The ethnographic atlases hitherto published in Europe have been created to meet the needs of particular countries and nations rather than with any prospect of comparative studies in mind. Thereby, it is difficult to find maps which are comparable when it comes to systematics and chronology. Therefore, we believe it necessary to interpret anew source materials deposited in Cieszyn workshop of the Polish Ethnographic Archives – to deepen the systematics of mapped phenomena along with their chronology and earmark for future development and studies topics that appear in other European atlases. The resultant maps are to compose an innovative edition, tentatively entitled The Atlas of Cultural Heritage of the Polish Village. The present article familiarizes readers with the concept of the planned endeavour, including aims, preliminary assumptions of the project, and the methodology of research.